Jeremy Robinson papers - Robinson, Jeremy, 1787-1834.
Correspondence, letterbook, diaries, journals, notebooks, and ships' records and papers concerning Robinson and the U.S. Navy, and his role in the struggle for independence in South America, particularly in Chile and Peru. Includes correspondence regarding his proposed history of Chile; supplying specimens for the Lyceum of Natural History, New York, N.Y.; and efforts to obtain government positions. Also includes ships' records relating to the Beaver (Flat-bottomed ship), USS Franklin (Ship of the line), and USS Ontario (Sloop of war). Correspondents include John Quincy Adams, Richard Alsop, James Biddle, Asbury Dickins, David Findlay, Henry Hall, Michael Hogan, Richard M. Johnson, Samuel L. Mitchill, Bernardo O'Higgins, John Bartow Prevost, Nathan Robinson, Richard Rush, William Thornton, Egbert Van Buren, and John Varnum.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Commercial agent at Lima, Callao, and elsewhere in South America.
Collection material in English.
Finding aid and card index available in the Library of Congress Manuscript Reading Room.
Forms part of: Peter Force papers and collection (Series 8D : entry 148).
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Alsop, Richard, -- 1761-1815 -- Correspondence; Biddle, James, -- 1783-1848 -- Correspondence; Dickins, Asbury, -- 1780-1861 -- Correspondence; Findlay, David -- Correspondence; Hall, Henry, -- active 1798-1800 -- Correspondence; Hogan, Michael, -- 1766-1833 -- Correspondence; Johnson, Richard M. -- 1781-1850 -- Correspondence; Mitchill, Samuel L. -- 1764-1831 -- Correspondence; O'Higgins, Bernardo, -- 1778-1842 -- Correspondence; Prevost, John Bartow, -- 1766-1825 -- Correspondence; Robinson, Nathan -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Thornton, William, -- 1759-1828 -- Correspondence; Van Buren, Egbert -- Correspondence; Varnum, John, -- 1778-1836 -- Correspondence; United States. -- Navy -- Foreign service -- South America; Beaver (Flat-bottomed ship); Franklin (Ship of the line); Lyceum of Natural History (New York, N.Y.); Ontario (Sloop of war); Ship's papers -- 19th century; Chile -- History; Chile -- History -- War of Independence, 1810-1824.; Peru -- History -- War of Independence, 1820-1829.; South America -- History -- 19th century; Commercial agents